Validation of the German Version of the Music-Empathizing-Music-Systemizing (MEMS) Inventory (Short Version) - Linnemann, Alexandra; Kreutz, Gunter; Gollwitzer, Mario; Nater, Urs M. (Frontiers in Behavioral Neuroscience, 2018)
Background: Kreutz, Schubert and Mitchell (2008) developed the Music-Empathizing-Music-Systemizing (ME-MS) Inventory to extend Baron-Cohen’s cognitive style theory to the domain of music. We sought to confirm the ME-MS construct in a German sample and to explore these individual differences in relation to music preferences. Methods: The German adaptation of the MEMS Inventory was achieved by forward and backward translation. A total of 1014 participants (532 male, age: 33.79 ± 11.89 years) completed the 18-item short version of the MEMS Inventory online. Confirmatory factor analysis (CFA) was performed and cut-off values were established to identify individuals who could be classified as ME, Balanced, or MS. Statistical analyses were used to examine differences in music preference based on music-related cognitive styles. Results: CFA confirmed two factors, ME and MS, with sufficiently good fit (CFI = 0.87; GFI = 0.98) and adequate internal consistency (Cronbach’s Alpha ME: 0.753, MS: 0.783). Analyses of difference scores allowed for a classification as either ME, Balanced, or MS. ME and MS differed in sociodemographic variables, preferred music genres, preferred reasons for music listening, musical expertise, situations in which music is listened to in daily life, and frequency of music-induced chills. Discussion: The German short version of the MEMS Inventory shows good psychometric properties. Based on the cut-off values, differences in music preference were found. Consequently, ME and MS use music in different ways, and the cognitive style of music listening thus appears to be an important moderator in research on the psychology of music.